Establishment of Regional Regulations For Coastal Area Rehabilitation As An Environmental Restoration Effort In Buru District - Tuhulele, Popy; Anwar, Arman; Waas, Armelia Febriyanti (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Research entitled